Relatives' experiences of the hospitalisation of older people with COVID‐19: A qualitative interview study. (14th February 2022) - Hoffmann, Eva; Specht, Kirsten; Elkjær, Mette; Kjær, Maria; Primdahl, Jette
Abstract: Background: During the COVID‐19 pandemic, visitors were restricted from hospitals, separating them from hospitalised friends and family to reduce the infection risk. Objectives: The objective was to explore how relatives of older people acutely admitted to hospital with COVID‐19 experienced being a relative, and how they felt about their contact with health care professionals (HCPs) when visitor restrictions prevented their physical presence in the ward. Method: This study employed a qualitative design. We used individual qualitative semi‐structured interviews and the participants were relatives of acutely admitted older people from three COVID‐19 wards in Denmark. A total of 18 relatives participated, 14 female and 4 male, aged between 45 and 83 years. The analysis was guided by Graneheim and Lundman's qualitative content analysis. Results: The analysis derived the following three themes: (1) the importance of trust in a period of uncertainty; (2) the meaning of contact with HCPs, and (3) active but at a distance—a balancing act. The participants' feelings of uncertainty were prominent. The unknown nature of the disease and the unusual situation challenged relatives' trust in HCPs and the health care system. Conclusions and relevance to practice: The findings highlight relatives' stress when the possibilities for visiting are restricted and the importance of trust in, and the relationship with HCPs. This study can strengthen HCPs' understanding of relatives' situation when older people are hospitalised during and after the COVID‐19 pandemic.